Alternation of bottom-up and top-down regulation in a natural population of an agromyzid leafminer, Chromatomyia suikazurae - Kato, M (Oecologia, 1994)
The population dynamics and the relative importance of bottom-up and top-down effects in a plant-leafminer-multiparasitoid interaction was studied between 1981 and 1990 in a natural forest in Kyoto, Japan. The leafminer, Chromatomyia suikazurae (Agromyzidae, Diptera), passed two generations (G1 and G2) on Lonicera gracilipes (Caprifoliaceae). The G1 population in February was free from parasitoid attack, and the mortality in G1 was mainly caused by resource limitation. Intraspecific competition for resources occurred at the larval stage in G1, and the larval mortality was density-dependent. The G1 adult density was resource-limited (the number of newly opened leaves), and its variability was lower than that of G2. The G2 population in April was not resource-limited but subject to intense attack by a species-rich parasitoid complex, and thus total mortality was much larger than that in G1. Significant density dependence was detected not in larval but in pupal mortalities, which were mainly caused by parasitism by parasitoids that attacked the pupa. The host population alternately experienced "bottom-up" effects during the larval stage in G1 and "top-down" effects during the pupal stage in G2. Overall population fluctuation was non-cyclic and mainly due to climatically-induced fluctuation of available plant resources in G1.